Effect of Dates of Planting, Bulb Size and Bulb Spacing on Growth and Seed Yield of Onion (Allium cepa L.) - BALRAJ SINGH; BHAGIRATH SINGH; B.S. TOMAR (Seed Research, 2026)
Field investigation were carried out to study the effect of planting time, bulb size and bulb spacing on plant growth and seed yield attributes of onion cultivar RO-1 during rabi of 1995-96, 1996-97 and 1997-98 at Agricultural Research Station, Durgapura (Jaipur) of Rajasthan Agricultural University (Bikaner). Maximum seed yield (10.95 q/ha) was obtained in 11th October planting followed by 1 October (10.05 q/ha). The bulb diameter (6.0x4.5 cm) and bulb spacing (45x30 cm) had given maximum seed yield of 9.87 q/ha and 9.76 q/ha, respectively. The maximum net return of Rs. 78145 per hectare and highest cost-benefit ratio of 1.0:3.36 were recorded when 4.5 x 3.0 cm diameter bulbs were planted at 45 x 30 cm spacing on 11 October for seed production of onion cultivar RO-1.